Metode Kashf dalam Penilaian Hadis: Studi Tashih Hadis di Kalangan Kaum Sufi - MUHAMMAD KUDHORI (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2018)
Method of assessing the soundness of hadith (Prophetic tradition) is not only limited to the rule that hadith’s experts formulate and employ. Sufi (Muslim mystical practioner) circles utilize hadith assessment method called kashf (mystical disclosure). This term literally means disclosing or uncovering a hijab (cover). Terminologcally speaking, it means the disclosure of unseen meanings and truth behind textual appearances. In hadith assess- ment context, kashf is a method used by Sufis since they do not follow hadith assessment principles and method constructed by hadith experts. The tradition of hadith assessment using kashf method is a new method that emerged after long time ago after Prophet’s hadiths were collected. This method emerged between the sixth century until the seventh century of Hijra. The first figure who applied this method is Ibn Arabi (558-638 H). Through kashf assessment method, hadith is considered sahih when it does not contra- dict shar‘ah rules. In adition, the hadith assessment using kashf needs to look at the position and quality of scholars who claim to obtain kashf. In turn, this method makes the role of sanad (chain of hadith transmission) smaller in terms of hadith determining the reliability of hadith. In kashf, sanad is directly linked to the Prophet SAW, even without having a person narrating a hadith. Moreover, the time interval between a Sufi who obtains kashf and the Prophet is long period of time. Furthermore, kasfh can make Jarh wa Ta‘dil (examining reliability of hadith narrators) trivial. The method of kashf is rejected by most of hadith’s experts, because it does not hold solid epistemology. The rules are relative, subjective and cannot be objectively defended.